2002
DOI: 10.1186/1471-2296-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for coughing in general practice: a questionnaire study to quantify and condense the reasons for prescribing

Abstract: Background: Antibiotics are being overprescribed in ambulant care, especially for respiratory tract infections (RTIs). Gaining insight into the actual reasons for prescribing remains important for the design of effective strategies to optimise antibiotic prescribing. We aimed to determine items of importance for the antibiotic prescribing decision and to make them operational for an intervention trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…[1][2][3][4][5] These suggestions have emerged from studies on how best to conduct consultations when antibiotics are deemed clinically inappropriate, but are nevertheless prescribed because of patient or parent expectations for antibiotics, as perceived by their physician. 3,6,7 Researchers have found that physicians rarely seek patient expectations, and by failing to do so, their perceptions of patient expectations can be unreliable and may indeed overestimate actual patient demand. 2,3,7,8 Various interventions seeking to facilitate the direct elicitation, and also the shaping, of patient expectations have been developed and evaluated.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] These suggestions have emerged from studies on how best to conduct consultations when antibiotics are deemed clinically inappropriate, but are nevertheless prescribed because of patient or parent expectations for antibiotics, as perceived by their physician. 3,6,7 Researchers have found that physicians rarely seek patient expectations, and by failing to do so, their perceptions of patient expectations can be unreliable and may indeed overestimate actual patient demand. 2,3,7,8 Various interventions seeking to facilitate the direct elicitation, and also the shaping, of patient expectations have been developed and evaluated.…”
mentioning
confidence: 99%
“…Physicians commonly ask their patients about the colour of their sputum and how unwell they are feeling to inform their decision of whether or not to prescribe an antibiotic for acute cough, based on the assumption that purulence is more likely to reflect a bacterial cause and predict improved outcomes from antibiotics [6][7][8]. Clinicians regard patients who feel both systemically unwell and who also produce discoloured sputum an even higher priority for an antibiotic prescription [9][10][11]. Guidelines identify purulent sputum as one of a cluster of clinical features that should alert clinicians to possible serious lung infection [12].…”
mentioning
confidence: 99%
“…Thus in patients with acute respiratory infections yellowish and greenish sputum as well as certain non-specific symptoms such as fatigue are strong predictors for antibiotic prescribing in primary care [4,11,12]. So far there has been no evidence that discoloured sputum is correlated with a bacterial aetiology of acute respiratory infections in otherwise healthy adults.…”
mentioning
confidence: 99%